My Experience as an Education Teacher - Revilla Cuñado, Avelino (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
My role as a priest in the episcopal delegation of teaching opened up a new horizon for me within the evangelising mission of the Church. The Church does not evangelise only through parishes. From the early beginnings of the Christian faith, the evangelisation has been linked to education. the presence of the Church in education unfolds into three dimensions: religious education at school, Catholic schools and Catholic educators. the coordinated action of these dimensions aims to implement an educational project whose centre is Jesus Christ as the perfect fulfilment of humankind.
Keywords: parish; education; school; religious education; catholic school; catholic educator; inculturation; person; truth; freedom; culture of encounter